Pengaruh Kepemimpinan Islami, Budaya Organisasi, Dan Religiusitas Terhadap Kinerja Karyawan Di Koperasi Simpan Pinjam Dan Pembiayaan Syariah Darumafatihil Ulum (KSPPS DMU JATIM) Pasuruan - Iis Nabila; Nur Hidayati; Eka Farida (UNIVERSITAS ISLAM MALANG, 2021)
Abstact Employee performance, both in quality and quantity, enables the vision, mission and goals of the organization to be achieved. The purpose of this study was to analyze the influence of Islamic leadership, organizational culture and religiosity on employee performance at KSPPS DMU Jatim Pasuruan. The population in this study was 95, and all of them were taken as samples. By using multiple linear analysis, the following results are obtained: simultaneously, the variables of Islamic leadership, organizational culture and religiosity have a significant positive effect on employee performance. partially, Islamic leadership variables, and organizational culture have a significant positive effect on employee performance. While the religiosity variable has no significant positive effect on employee performance. Keywords : Islamic Leadership, Organizational Culture, Religiosity, Employee Performance